Analisis Kualitas Layanan Jasa Transportasi Online (Studi Pada Pengguna Gojek Di Daerah Istimewa Yogyakarta) - Damayanti, Dila; Maharani, Maharani (Kajian Ekonomi dan Bisnis, 2020)
The very rapid development of technology has made internet users increase, thus inviting the presence of online transportation. Gojek is an online transportation service business that is growing rapidly at this time. As one of the most trusted online transportation services, Gojek must have an effective and innovative strategy to get and retain its customers. This study aims to determine how the quality of Gojek’s online transportation services on customer satisfaction (a study of Gojek users in the Yogyakarta Special Region). Researchers used 80 respondents as samples in the study who were customers of Gojek online transportation in the Umbulharjo district of Yogyakarta City. The problems raised in this study were (1) identifying customer characteristics, (2) analyzing the level of interest and customer satisfaction. The data analysis used is descriptive analysis, Importance Performance Analysis (IPA). The results of the Importance Performance Analysis (IPA), there are several variables of the quality of Gojek online transportation services in quadrant II with an average IKP value of 68.25%. This means that users of the Gojek online transportation service in Umbulharjo District, Yogyakarta Province are quite satisfied with the performance of Gojek company drivers.